Współczesne oblicza władzy politycznej – kilka uwag wstępnych - Żyromski, Marek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The author discusses the issues of authority (in particular political authority), approaching it as a fragment of a highly complex and extensive subject. He emphasizes that it is extremely difficult to find a notion (as well as a phenomenon, or rather a process) that is equally significant in political science, and yet one that is simultaneously so elusive and difficult to verify pragmatically as authority. He stresses that it has accompanied Homo sapiens since their very beginnings. The basement of the National Museum in Addis Ababa, the capital of Ethiopia, exhibits the remnants of a skeleton of our great-, great-… (and so on) grandmother, ‘Lucy.’ As we observe the behavior of our hominid relatives (from whom the notion of ‘alpha male’ has been transferred to contemporary politics) it is hard to avoid the idea that Lucy had to fight for her position. Authority permeates all realms of social existence and is present in all historical and contemporary societies. On the most comprehensive macroscale, authority is the core aspect of international political relations, as well as economic relations between states or transnational companies. On a microscale, authority is exercised in the most basic human contacts and interactions. It is manifested as the authority of state over its citizens, superiors over subordinates, teachers over students, parents over children, and girls over those infatuated with them. It is this universal and common nature of the phenomenon (or process) of authority which occurs both inside and outside politics, and which generates such profound difficulties.